PENGARUH LAMA PERENDAMAN TELUR DALAM LARUTAN TEPUNG TESTIS SAPI TERHADAP JANTANISASI IKAN RAINBOW (Melanotaenia sp.) - Setiawan, Arif Bayu; Susilowati, Titik; Yuniarti, Tristiana (Journal of Aquaculture Management and Technology, 2017)
Ikan hias pelangi (rainbow) merupakan salah satu ikan hias papua yang mempunyai bentuk dan warna yang unik yang memilki jenis yang sangat banyak ada yang sudah diberi nama dan ada yang belum, juga mempunyai nilai jual yang lumayan dan merupakan komoditas ekspor. Penelitian ini bertujuan untuk mengetahui pengaruh lama perendaman telur dalam tepung testis sapi dan mengetahui waktu yang terbaik terhadap jantanisasi ikan rainbow (Melanotaenia sp.). Penelitian ini dilaksanakan di APPIHIS Semarang pada bulan Oktober- Desember 2016 dengan metode penelitian menggunakan rancangan acak kelompok dengan 5 perlakuan dan 3 ulangan. Lama waktu perendaman yaitu perlakuan A selama 0 jam atau tanpa perendaman tepung testis sapi, perlakuan B 24 jam, perlakuan C 36 jam, perlakuan D 48 jam dan perlakuan E selama 60 jam dengan dosis yang sama yaitu sebanyak 60 ppm. Data yang diambil adalah persentase kelamin jantan, betina, kelulushidupan (SR) dan kualitas air. Analisis data menggunakan ANNOVA dan apabila terdapat pengaruh yang nyata makan dilanjutkan dengan uji Duncan. Persentase kelamin jantan dan betina didapatkan perlakuan A sebesar 28,43%±5,38; 71,57%±5,38, perlakuan B sebesar 62,67%±3,69; 37,33%±3,69, perlakuan C sebesar 59,92%±1,73; 40,08%±1,73, perlakuan D sebesar 44,27%±2,31; 55,73%±2,31 dan perlakuan E sebesar 33,06%±0,67; 66,94%±0,67. Kelulushidupan (SR) didapatkan pada perlakuan A sebesar 90,81%±2,06, perlakuan B sebesar 97,22%±0,92, perlakuan C sebesar 93,72%±1,09, perlakuan D sebesar 93,85%±1,35 dan perlakuan E sebesar 95,99%±1,68. Kesimpulan dari penelitian ini adalah lama perendaman telur yang berbeda berpengaruh terhadap jantanisasi ikan rainbow dan lama perendaman terbaik adalah pada perlakuan B dengan lama perendaman selama 24 jam menghasilkan persentase jantan sebesar 62,67%±3,69.Rainbow fish is one of the ornamental fish Papua that have unique shape and color who have very many species have already been named and there is not yet, also has a hefty selling value value and is an export commodity. This research aims to determine the effect of soaking in the testes flour cows and knowing the best time to jantanisasi rainbow fish (Melanotaenia sp.). This research was conducted in APPIHIS Semarang in October-December 2016 with the research method using a grou randomized design with 5 treatments and 3 replications. Length of time a soaking is without soaking the flour treatment A cow testicle, treatment B 24 hours, treatment C 36 hours, 48 hours of treatment D and E for 60 hours of treatment with the same dose as many as 60 ppm. Data taken is percentage of male genitals, female, survival rate (SR) and water quality. Analysis of data using ANOVA and if there is significant differences meal continue by Duncan test. The percentage of male and female A treatment obtained by 28.43% ± 5.38; 71.57% ± 5.38, treatment B by 62.67% ± 3.69; 37.33% ± 3.69, C treatment amounting to 59.92% ± 1.73; 40.08% ± 1.73, treatment D amounted to 44.27% ± 2.31; 55.73% ± 2,31 and treatment E of 33.06% ± 0.67; 66.94% ± 0.67. Survival rate (SR) be obtained at treatment A of 90.81% ± 2.06, treatment B by 97.22% ± 0.92, C treatment amounting to 93.72% ± 1.09, treatment D amounted to 93.85% ± 1,35 and treatment E of 95.99% ± 1.68. The conclusions of this study are different eggs soaking time affects the rainbow and old fish maskulinisasi best soaking is in treatment B with old soaking for 24 hours resulted in the percentage of males by 62,67%±3,69. Rainbow fish is one of the ornamental fish Papua that have unique shape and color who have very many species have already been named and there is not yet, also has a hefty selling value value and is an export commodity. This research aims to determine the effect of soaking in the testes flour cows and knowing the best time to jantanisasi rainbow fish (Melanotaenia sp.). This research was conducted in APPIHIS Semarang in October-December 2016 with the research method using a grou randomized design with 5 treatments and 3 replications. Length of time a soaking is without soaking the flour treatment A cow testicle, treatment B 24 hours, treatment C 36 hours, 48 hours of treatment D and E for 60 hours of treatment with the same dose as many as 60 ppm. Data taken is percentage of male genitals, female, survival rate (SR) and water quality. Analysis of data using ANOVA and if there is significant differences meal continue by Duncan test. The percentage of male and female A treatment obtained by 28.43% ± 5.38; 71.57% ± 5.38, treatment B by 62.67% ± 3.69; 37.33% ± 3.69, C treatment amounting to 59.92% ± 1.73; 40.08% ± 1.73, treatment D amounted to 44.27% ± 2.31; 55.73% ± 2,31 and treatment E of 33.06% ± 0.67; 66.94% ± 0.67. Survival rate (SR) be obtained at treatment A of 90.81% ± 2.06, treatment B by 97.22% ± 0.92, C treatment amounting to 93.72% ± 1.09, treatment D amounted to 93.85% ± 1,35 and treatment E of 95.99% ± 1.68. The conclusions of this study are different eggs soaking time affects the rainbow and old fish maskulinisasi best soaking is in treatment B with old soaking for 24 hours resulted in the percentage of males by 62,67%±3,69.